Causal relationship between FDI and poverty reduction in South Africa - M. T. Magombeyi; N. M. Odhiambo (Cogent Economics & Finance, 2017)
This study investigates the causal relationship between poverty reduction and foreign direct investment (FDI) inflows in South Africa using time-series data from 1980 to 2014. The main objective of this study is to establish the direction of causality between FDI and poverty reduction, which is important to policy-makers as it identifies which variable to target first. Gross domestic product is included as an intermittent variable giving a trivariate framework. Employing the autoregressive distributed lag (ARDL) bounds testing approach to cointegration and ECM-based causality tests, the results from this study reveal a distinct unidirectional causality from poverty reduction to FDI in both the short run and the long run when poverty reduction is measured by life expectancy and infant mortality rate. However, the study failed to find any causality, irrespective of the time considered, when poverty reduction is measured by household consumption expenditure. It can be concluded therefore, that the causal relationship between FDI and poverty reduction is sensitive to the proxy used to measure the level of poverty reduction.
Keywords: F21; I32; 330; South Africa; household consumption expenditure; life expectancy; infant mortality rate; granger-causality